Students’ Errors in Using language Features in Writing a Personal Recount Text at SMPN 5 Padang Panjang - Kifli, Rifa Nabila; Rani, Yati Aisya (Journal of English Language Teaching, 2024)
This reserach aimed to find out students’ errors in using language features in wrting a personal recount text. This research employed a descriptive research. The resercher adapted the theory of language features form Gerot and Wignell (1994), Barwick (1998), and Derewianka & Jones (2016). The paericipants were 42 eighth-grade students of SMPN 5 Padang Panjang. According to the research findings, the errors made by the students in using language features from the three language features; specific participants, simple past tense and adverbial phrases and connectives were the absence of specific pronoouns and verbs, the incorrect use, form and order, the addition of another verbs.